Sosialisasi Literasi Digital Sejak Dini: Pengabdian - Putra, Juni Adi; Simatupang, Erna Juliana; Heru, Djimmy; Hasanah, Uswatun; Septiandini, Karina; Rachma, Alyaa; Salsabila, Nazla Sapa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The rapid advancement of digital technology has had a significant impact on the education sector, particularly for young children who belong to Generation Alpha. This generation grows and develops in an environment that is closely connected to technology use, which makes appropriate guidance essential so that technology can be used wisely and responsibly. At the same time, low levels of literacy, including reading literacy and digital literacy, as well as the increasing risk of deviant behavior in digital spaces, have become challenges that need to be addressed from an early stage. Therefore, this community service activity focuses on the socialization of digital literacy from an early age for elementary school students. The activity aims to foster an understanding of the importance of literacy, develop reading, writing, and storytelling skills, and cultivate a literacy culture within the school environment. The implementation methods include interactive material delivery, group discussions, hands-on literacy activities, and evaluation through pre-tests and post-tests to measure participants’ improvement in understanding. The results indicate an increase in students’ knowledge of literacy and digital literacy, accompanied by a growing interest in reading and writing in daily learning activities. Thus, this activity is expected to contribute to strengthening the literacy culture in elementary schools and to serve as a positive form of collaboration between higher education institutions and schools in preparing a generation with strong literacy skills in the digital era.